Battling and Rescuing as Double Heroism in Ayo Gorkhali: A History of the Gurkhas by Tim I. Gurung - Rai, Ram Prasad (SCHOLARS: Journal of Arts & Humanities, 2021)
The main aim of this paper is to study the dual heroism of the Gorkhas: ‘battling’ and ‘rescuing’ in the book Ayo Gorkhali: A History of the Gurkhas by Tim I. Gurung from the evolutionary perspective. The book is about the Gorkhas’ bravery in battling as well as rescuing exhibited in wars around the world because of which they brought victory and power to Britain. Despite their defeat in the Anglo-Nepal War (1814-1816), the Gorkhas were able to impress the British authority for their bravery, dedication and discipline. The British East India Company began to recruit the Gorkhas in their army. They succeeded to suppress robberies, banditries and mutinies and establish peace and order in the society. In every theatre of war including the First and Second World Wars, the Gorkhas battled bravely for Britain and kept her name always high in the world. In this paper, the researcher has consulted books, journal articles and documentaries related to the Gorkhas and their heroic performance in wars. The Gorkhas are found to be brave in both ‘fighting’ as well as ‘making rescue’ of their co-warriors, officers and civilians during the wars. They have been known as the ‘bravest of the brave’ in the world. This paper will be new insights for the future researchers in the particular area of study.